The 9E Learning Cycle Model as a 21st Century Learning Solution: An Analysis of Its Impact on Improving High School Students' Habits of Mind in Digestive System Material - Haka, Nukhbatul Bidayati; Rahayu, Anggun Septi; Pratama, Anisa Oktina Sari; Masya, Hardiyansyah; Rakhmawati, Ismi (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
Background: Habits of Mind require calm and confidence. High cognitive anxiety can hinder biology learning. This study analyzes the 9E Learning Cycle Model to improve 11th-grade students' Habits of Mind on the digestive system topic. Methods: The research employs a Quasi-Experimental method with a Pretest-Posttest Control Group Design. The research sample consists of the 11th-grade students from SMA A in Bandar Lampung, selected through Cluster Random Sampling. The research instruments include multiple-choice tests and a habits of mind questionnaire. Data is analyzed using Independent Samples t Test. Results: It is revealed that the Learning Cycle 9E Model Based on Performance Assessment is a solution to improve high school students' habits of mind in biology learning, as evidenced by normally distributed and homogeneous data, with a calculated significance value of 0.001 < 0.05 (α). Conclusions: The findings of this study are expected to serve as a literacy source that encourages readers to understand and delve deeper into the Learning Cycle 9E model based on performance assessment that can be applied to enhance students' habits of mind. Additionally, the results of this research can be used as input for educators to enhance the quality of learning activities, particularly in the subject of biology. The implications of this study indicate that the use of the 9E Learning Cycle Model can significantly improve students' critical thinking, creative thinking, and self-regulation skills, which are essential for preparing them to face 21st-century challenges.